Serum uromodulin and mortality risk in patients undergoing coronary angiography - Delgado Gonzales de Kleber, Graciela; Kleber, Marcus E.; Krämer, Bernhard; März, Winfried (Journal of the American Society of Nephrology, 2017)
The mucoprotein uromodulin is the most abundant protein in mammalian urine and has important roles in ion transport, maintenance of water and electrolyte balance, and clearance of bacteria from the urinary tract. Low urinary uromodulin concentrations have been associated with increased mortality risk. However, measuring uromodulin in urine has several preanalytic drawbacks, and sensitive assays for the detection of uromodulin in blood have become available. In this study, we investigated the association of serum uromodulin concentration with cardiovascular biomarkers and mortality risk in a large cohort of patients referred for coronary angiography. Uromodulin concentrations were available in 3057 of 3316 participants of the Ludwigshafen Risk and Cardiovascular Health Study. Higher serum uromodulin concentration associated with a favorable metabolic profile, lower prevalence rates of comorbidities (arterial hypertension, diabetes mellitus, and heart failure), and a lower risk for 10-year mortality, with hazard ratios (95% confidence intervals) of 0.65 (0.54 to 0.78), 0.71 (0.58 to 0.88), and 0.57 (0.45 to 0.73) in the second, third, and fourth quartiles, respectively, compared with the first quartile. The association with reduced mortality was independent of other cardiovascular risk factors, including eGFR, and stronger after adjustment for the genotype of the rs12917707 polymorphism at the UMOD locus. Adding serum uromodulin concentration to established cardiovascular risk prediction scores improved risk prediction. Uromodulin may, therefore, be a useful marker for cardiovascular and renal health.